2003
DOI: 10.1007/s00276-003-0105-2
|View full text |Cite
|
Sign up to set email alerts
|

A very rare anatomic variation of the left brachiocephalic vein: left retro-aortic brachiocephalic vein with tetralogy of Fallot

Abstract: An anomalous course of the left brachiocephalic vein behind the aortic arch was identified in a patient with tetralogy of Fallot. A 6-year-old male patient had been admitted to the hospital with a diagnosis of tetralogy of Fallot and patent foramen ovale. At the beginning of the operation the left brachiocephalic vein could not be found. The pericardium was opened longitudinally and there was no persistent left superior vena cava. After careful examination, the left brachiocephalic vein was found behind the ao… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 11 publications
0
18
0
2
Order By: Relevance
“…Right sided aortic arch is another abnormality seen with high frequency in ALBCV patients. This aortic abnormality has been reported in ALBCV patients as high as 46% [14], 70% [19], 77% [3] and 86% [10]. In a study by Choi et al [4] it was shown that the presence of ALBCV in other congenital heart anomalies such as TOF, VSD or pulmonary atresia is associated with higher incidence of right sided aortic arch.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…Right sided aortic arch is another abnormality seen with high frequency in ALBCV patients. This aortic abnormality has been reported in ALBCV patients as high as 46% [14], 70% [19], 77% [3] and 86% [10]. In a study by Choi et al [4] it was shown that the presence of ALBCV in other congenital heart anomalies such as TOF, VSD or pulmonary atresia is associated with higher incidence of right sided aortic arch.…”
Section: Resultsmentioning
confidence: 78%
“…Most of the left anterior cardinal veins should disappear and new transverse anastomotic channels by capillary plexus should be made in order to drain the left side of head and neck and left arm. If the aortic arch does not shorten during embryological development, it will prevent the development of transverse venous plexus and leads to formation of an anomalous course of innominate vein [6,12,16,17,19].…”
Section: Resultsmentioning
confidence: 99%
“…The male to female ratio was almost 1:1. Eighty-eight patients had tetralogy of Fallot or its analogous anomalies (Elami et al, 1995;Ito et al, 2001;Mill et al, 1993;Yilmaz et al, 2003), and 16 patients had VSD with pulmonary atresia (Choi et al, 1990;Ming et al, 2009;Morhy Borges Leal et al, 2002). Over 80% of the patients had the so-called conotruncal cardiac anomaly.…”
Section: Discussionmentioning
confidence: 96%
“…The sub-aortic LBV was described previously (Adachi 1933;Kitamura et al 1981;Yoshida et al 1984;Ohkubo et al 1991;Yamaki et al 1994;Gülsün et al 2003;Yilmaz et al 2003) and has an incidence of approximately 0.2% among necropsy cases with congenital heart diseases (Gerlis and Ho 1989) and 0.98% among patients with congenital heart diseases only (Choi et al 1990). Typically, a connection between the bilateral anterior cardinal veins develops anterior to the ascending aorta to form the pre-aortic LBV in early fetal life (49-56 days gestation).…”
Section: Discussionmentioning
confidence: 91%